Cultural Factors as a Challenge in Emergency Management - Miglinė, Vilma; Rakšnys, Adomas Vincas (Jaunųjų mokslininkų darbai, 2016)
The study deals with cultural problems related to emergency issues. Its aim is to analyse cultural factors that have influence upon emergency management. Objectives: to discuss the concept of culture in the context of emergency management, to evaluate challenges that different cultures face in emergency management, to emphasize the ethnic and cultural factors that have influence upon the mental health of victims. Research methods: literature analysis, data synthesis and generalization. Having analyzed emergency management practices in various countries it was found that the influence of cultural factors may be positive and negative. The main cultural factors are: religious beliefs, a language barrier, attitudes towards gender and social class. A person’s ability to adapt, reconcile himself to losses, voluntare are positive factors. It is important to note that emergency situations may rebalance the affected communities, put the social system at risk, lead to mental health problems. It was found that the above mentioned factors manifest themselves differently in different cultures therefore it is necessary to know the cultural context while providing victims of emergencies with support.